2016
DOI: 10.1089/zeb.2016.1261
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Toxic Effects of Bisphenol A and Products of Its Degradation: Zebrafish (Danio rerio) Embryo Test and Molecular Docking

Abstract: Bisphenol A (BPA) acts as an endocrine-disrupting compound even at a low concentration. Degradation of BPA could lead to the formation of toxic products. In this study, we compare the toxicity of BPA and seven intermediate products of its degradation. The accuracy of three molecular docking programs (Surflex, Autodock, and Autodock Vina) in predicting the binding affinities of selected compounds to human (ERα, ERβ, and ERRγ) and zebrafish (ERα, ERRγA, and ERRγB) estrogen and estrogen-related receptors was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…It was shown that HQ exhibits a higher toxicity compared with BPA in relation to human promyelocytic leukemia (HL-60) and human oral squamous cell carcinoma (HSC-2) cells (Terasaka et al 2005 ). However, zebrafish embryo toxicity test showed that HQ was much less toxic then BPA (Makarova et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that HQ exhibits a higher toxicity compared with BPA in relation to human promyelocytic leukemia (HL-60) and human oral squamous cell carcinoma (HSC-2) cells (Terasaka et al 2005 ). However, zebrafish embryo toxicity test showed that HQ was much less toxic then BPA (Makarova et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, zebrafish have been used to study the toxic effects of BPA and the products of its degradation (Makarova, Siudem, Zawada, & Kurkowiak, 2016). The degradation products of BPA were found to have lower binding affinity for both human and zebrafish estrogen receptors than BPA itself but one degradation product, 4-isopopylphenol, was predicted to have a higher binding affinity for the human ERRγ and slightly lower affinity for zebrafish ERRγA.…”
Section: Pathways and Mechanisms Of Toxicant-induced Diseasementioning
confidence: 99%
“…A relatively newer discipline, and highly hot topic, which has become increasingly important in recent years, is the computer-aided in silico toxicity prediction of drugs, food additives, or various industrial chemicals for which a previous wet-lab toxicity outcome is available. For this purpose, QSAR, the CAESAR project, and other virtual screening methods such as docking (i.e., AutoDock, Surflex) software have found wide use in the last decade [82][83][84]. While these software use special parameters (e.g., genetic algorithms), the details of these parameters do not fall into the scope of the main subject of this review article.…”
Section: In Silico Prediction Of Chemical Toxicitymentioning
confidence: 99%